Cultural Accessibility and public policies in cultural spaces (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article refers to the research on Cultural Accessibility and public policies, whose objective is to understand the accessibility to/with/from the disabled person in Xisto Bahia Space, located in the city of Salvador - BA. Thus, for data collection, an interview was conducted with the manager, cultural producer and artist Ninfa Cunha. Thus, for data collection, in addition to conducting a bibliographic review on the theme in question, using the laws on Cultural Accessibility and its consequences. Due to this bias, the article seeks to analyze the importance of the dimensions of atheusinal, communicational and architectural accessibility for access to the cultural space. Finally, we highlight the obstacles faced by both the artist and the spectator with disabilities to enjoy the accessible cultural space, as well as the difficulties encountered by managers and cultural producers to make the cultural space accessible.
Keywords: Cultural Accessibility; People with disabilities; Cultural spaces; Xisto Bahia Space